Supporting organizations to improve migrants' access to health services in New York City - Kathleen Cravero; L. Ansley Hobbs; Elisabeth Manipoud Figueroa; Diana Romero (Elsevier, 2024)
Purpose: To survey community-based migrant-serving organizations (MSOs) in New York City (NYC) regarding their early experiences during the COVID-19 pandemic and perspectives on academic collaborations. Methods: We developed and emailed a survey via Qualtrics (12/2020-1/2021) to 122 MSOs in NYC collecting data about the organizations; challenges posed by COVID-19; and interest in potential intersectoral collaboration. Descriptive analysis focused on the pandemic's impact on service provision, type of MSO, and organizational capacity. Results: Thirty-eight MSOs participated (RR=31%). COVID-19-related challenges included limited staff capacity, organizational funding, and technological and resource limitations of communities served. Organizational capacity correlated with types of services offered: smaller organizations offered health and social services, while larger organizations focused on education and employment. MSOs indicated interest in collaboration on migrant policy advocacy and communications, access to interns, and resources regarding best practices and policies. Conclusions: MSOs in NYC have struggled with funding, staffing, and service provision. They specified fruitful areas for collaboration with academic research institutions. Implications: Development of an academic-based migrant health resource hub will serve an identified need among MSOs in NYC.